To the question on judicial examination of psychological signs of reliability of indications in criminal trial - Fourmanov, Igor A.; Metlickij, Igor E. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
In article on the basis of the analysis of modern legal and psychological approaches, prospects of application of a new kind of judicial examination – judicial examination of psychological signs of reliability of indications in criminal trial are considered. From a position of the system approach the structure of psychological criteria of an estimation of reliability of indications in criminal trial, proceeding from that functional loading which they bear in criminalistics and legal psychology is offered. The methodology of judicial examination of psychological signs of reliability of indications in criminal trial is theoretically proved.
Keywords: sources of proofs; indications of suspects; the witnesses who have suffered; lie verification; signs of conscious insincerity